Learning from the COVID-19 pandemic in Italy to advance multi-hazard disaster risk management - Terzi, Stefano; De Angeli, Silvia; Miozzo, Davide; Massucchielli, Lorenzo Stefano; Szarzynski, Joerg; Carturan, Fabio; Boni, Giorgio (Progress in Disaster Science, 2022)
COVID-19 challenged all national emergency management systems worldwide overlapping with other natural hazards. We framed a ‘parallel phases’ Disaster Risk Management (DRM) model to overcome the limitations of the existing models when dealing with complex multi-hazard risk conditions. We supported the limitations analysing Italian Red Cross data on past and ongoing emergencies including COVID-19 and we outlined three guidelines for advancing multi-hazard DRM: (i) exploiting the low emergency intensity of slow-onset hazards for preparedness actions; (ii) increasing the internal resources and making them available for international support; (iii) implementing multi-hazard seasonal impact-based forecasts to foster the planning of anticipatory actions. •We analyse Italian COVID-19 management data from the Italian Red Cross.•We propose a model with parallel phases for multi-hazard DRM.•The model accounts for the management of complex sudden- and slow-onset dynamics.•We identify three main guidelines for advancing multi-hazard DRM.